Advancing the understanding of allergic contact dermatitis: from pathophysiology to novel therapeutic approaches - Tramontana, Marta; Hansel, Katharina; Bianchi, Leonardo; Sensini, Chiara; Malatesta, Nicolò; Stingeni, Luca (Frontiers in Medicine, 2023)
Allergic contact dermatitis (ACD) is a common inflammatory skin disease that, especially when the condition becomes chronic, has a high impact on the quality of life and represents a significant disease burden. ACD represents a type IV delayed-type hypersensitivity reaction that is triggered by contact with an allergen in previously sensitized individuals through the activation of allergen-specific T cells. In the acute phase, it is characterized by eczematous dermatitis, which presents with erythema, edema, vesicles, scaling, and intense itch. Non-eczematous clinical forms are also described (lichenoid, bullous, and lymphomatosis). Lichenification is the most common clinical picture in the chronic phase if the culprit allergen is not found or eliminated. ACD can be associated with both occupational and non-occupational exposure to allergens, representing approximately 90% of occupational skin disorders along with irritant contact dermatitis. Patch testing with suspected allergens is required for a diagnosis. Metals, especially nickel, fragrance mix, isothiazolinones, and para-phenylenediamine, are the most commonly positive allergens in patients patch tested for suspected ACD. The treatment goal is to avoid contact with the culprit agent and use topical and/or systemic corticosteroid therapy.